Assessing applicability of isotope-ratio mass spectrometry (IRMS) for geographical identification of whole milk - I. V. Podkolzin; A. I. Solovyev (Ветеринария сегодня)
Applicability of isotope-ratio mass spectrometry of light elements (C, N, О, H) has been assessed for identification of geographical origin of Russian milk collected in different parts of the Russian Federation (235 sample of whole milk). Quantitative assessment was carried out in a series of statistical tests based on nonparametric dispersion analysis.